The Effect of Clustering Technique on Students Achievement in Writing Recount Text - Hidayatullah Hidayatullah; Minarni Minarni (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of the study to find out whether or not clustering technique was effective on students’ achievement in writing recount text. Methodology: This research used quasi-experimental research. The sample was selected from the population that consisted of five classes at the tenth grade. The researcher selected X5 as experimental class and X4 as control class. Purposive sampling was used by the the researcher to select a sample. Purposive sampling was used by the the researcher to select a sample. The researcher used a test as research instrument.The data were analyzed by using descriptive statitics and t-test (independent sample test) in order to calculate the pretest and posttest results. Main Findings: It can be concluded that the students got better achievement by using clustering technique in writing recount text. Novelty/Originality of this study: The result of this research could inform to teachers that using of clustering technique was able to increase the student’s writing skill. It also could be used to help the teachers in developing student’s writing skill before they started to write.